2018
DOI: 10.1038/s41598-017-18852-3
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a mental lexicon with cochlear implants: an ERP study with young children

Abstract: In the present study we explore the implications of acquiring language when relying mainly or exclusively on input from a cochlear implant (CI), a device providing auditory input to otherwise deaf individuals. We focus on the time course of semantic learning in children within the second year of implant use; a period that equals the auditory age of normal hearing children during which vocabulary emerges and extends dramatically. 32 young bilaterally implanted children saw pictures paired with either matching o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 61 publications
5
16
0
7
Order By: Relevance
“…The study reported in Chapter 4 is unique, with respect to its focus on the specific subset of hearing-impaired children, who have CIs and use spoken language. The findings are, however, supported by previous research findings in which a significant N400 effect was demonstrated in younger children with CIs, who used a mix of sign and spoken language (Kallioinen et al, 2016;Vavatzanidis, Murbe, Friederici & Hahne, 2018).…”
Section: Semantic Processing In Children With Cochlear Implants 'Semsupporting
confidence: 87%
See 3 more Smart Citations
“…The study reported in Chapter 4 is unique, with respect to its focus on the specific subset of hearing-impaired children, who have CIs and use spoken language. The findings are, however, supported by previous research findings in which a significant N400 effect was demonstrated in younger children with CIs, who used a mix of sign and spoken language (Kallioinen et al, 2016;Vavatzanidis, Murbe, Friederici & Hahne, 2018).…”
Section: Semantic Processing In Children With Cochlear Implants 'Semsupporting
confidence: 87%
“…In contrast, the effect was absent prior to the activation of the second CI, during which time she completed the task having only unilateral auditory stimulation (Key et al, 2010). While not conclusiveespecially given the lack of TH control group (Vavatzanidis et al, 2018) and single case sample size (Key et al, 2010)taken together, the results from these studies provide some context for the early language development of children with significant hearing loss. Cochlear implants allow this population a means of accessing spoken language, which may therefore facilitate the development of aural-based semantic representations.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Of these, the N400 component is known to increase negatively in response to semantic violations [9] and is a potential objective measure of listening effort. In semantic mismatch, the ERP produces increased negativity approximately 400 ms post onset of the stimuli of interest and is called the 'N400 effect' [10]. Although the most common paradigm is a congruency test using sentence material, N400 is also elicited by semantic priming tasks [11] or by matching semantic material to a visual display [12].…”
Section: Effect Of Speech Degradation and Listening Effort In Reverbementioning
confidence: 99%